(untitled) (Altre Modernità, 2009)
Paris is a widespread urban system: a space and a landscape which have progressively become polycentric, according to logics of spatial organization which are in syntony with the city’s historical development, from the center towards its peripheral areas. The center has always been the privileged ensemble of famous places which record the succession of the different historical phases of the city. The peripheral areas, on the other hand, are spaces marked by social imbalance, ethnic miscegenation and segregation. There are therefore two Parises: the one of the symbolic landmarks and of the vivacity of its social encounters and the one of the immigrants and of their exclusion. Both these Parises, in spite of their striking differences, are involved in a process of renovation and reassembling. Through the years, several modernizing projects have touched various sectors of the city, and the criteria of intervention have been adapted to their changing problems. Among this criteria is the notion of lasting development, which should realize a link between the old and new areas of the city and, and at the same time, make the urban environment easier to access by all its inhabitants. The social and environmental commitment on the one hand improves the livability of the public areas and empowers traditional collective practices, while on the other helps contextualize the remains of the past on the basis of modern exigencies such as the improvement of the living conditions and a steadily increasing pollution safeguard. In order to understand the complex urban texture of a city like Paris we should proceed with an epistemological, aestetic, political and social interpretation which also takes into consideration the economic and territorial components, because all these interwoven aspects concur to the richness of the metropolitan landscape of Paris. The historico-geographic stratification of the French capital is the very basis of its inestimable value and can become a key factor of its modernity.